A Glaciação plistocénica na Serra do Gerês - Ferreira, António Brum (2000)
THE PLEISTOCENE GLACIATION OF SERRA DO GERÊS (NORTHWEST PORTUGAL) - Studies made by Schmidt-Thomé (1973, 1978) and Coudé-Gaussen (1978, 1979, 1981) which put forward the explanation of a Pleistocene glaciation in the Gerês mountain gave rise to lively controversy. In order to clarify the problem, the authors of the present study selected two lines of research: 1)detailed geomorphologic mapping; and 2)laboratory analysis of the glacial deposits. This sedimentological study, which had not been carried out before in the area, proved to be very significant for the diagnosis of the style and extent of the glaciation. We can confirm the Serra do Gerês glaciaion. The vestiges are particularly clear and important on the Eastern side of the mountain and in the Fafião valley, where the most important glacigenic sediment complex is found. At the glaciation maximum, an ice dome reached the thickness of some 150m in both the Couce and the Compadre areas, from whence outlet glaciers radiated into the main peripheral valleys. At that time the upstream sector of the Homem Valley glacier must have reached the thickness of about 300m. Recent absolute dating, using cosmogenic isotopes in glaciated granitic surfaces, suggested that the glaciation maximum in the Gerês is older than the Last Glaciation.